Self-Mention and Engagement Mechanisms of (Negative) Evaluation in Linguistics Academic Reviews: A Diachronic Insight - Vučićević, Ana Lj.; Rakić, Aleksandra D. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper is a small-scale exploratory study of self-mention and engagement markers in the reviews published in a reputable Serbian academic journal "South Slavic Philologist" during the 1920s. Using Hyland’s (2005a; 2005b) classification, we identified context-prominent mechanisms of author self-reference and reader inclusion in fifteen academic reviews of diverse disciplinary contributions. The reviewers explicitly present their assessments and position their claims as expertise-based and unarguable. Readers are invited to participate, pose questions and consult other sources in the field just to reach the same conclusions the authors had reached previously. The dialogue the reviewers initiate with readers serves to point out shared values or expertise that leads to the impression that readers and reviewers also share (negative) perspectives on the matters the reviewed material raises. The findings might indicate some of the stylistic preferences of academic communication (in this journal) at the time.
Keywords: academic reviews; “South Slavic Philologist”; negative evaluation; criticism; self-mention; engagement; diachronic perspective